RANCANG BANGUN SISTEM UJIAN ONLINE BERBASIS WEB STUDI KASUS : MDTA NURUL HUDA PULOKALAPA: Information Systems;Online Exam. - Rifai, Ahmad; Suryani, Nining (LP2M Universitas Nurdin Hamzah, 2022)
The development of science and technology in the current era of globalization is growing rapidly and rapidly. Responding to progress that continues to grow, with web technology an information system can be designed that is able to facilitate school activities. Exams are activites carried out by educational units to agencies to measure the competencies and abilities of the examinees. The exam process conducted by MDTA Nurul Huda is still done manually, by utilizing advances in computer technology, online exams can be conducted, so that the exam process can be carried out effectively and efficiency. The purpose of this research is to design and implement an online exam information system for the exam process at MDTA Nurul Huda. The data collection methods used in the preparation of this final project are observation, literature study and interviews. The design of this online exam information system is the best solution to achieve this. An activity that is effective and efficient in supporting activities at this school, the point is that exams with an online system are more practical, easier and make students more focused.